Autoantibody production in pregnancy: relationship with mRNA BNT162b2 immunization, active COVID-19, and pre-eclampsia - Silva, Mauro César da; Diniz, George Tadeu Nunes; Correia, Maria Júlia da Silva; Silva, Neila Caroline Henrique da; Barbosa, Camila Rodrigues de Melo; Ferreira, Ana Laura Carneiro Gomes; Melo, Maria Inês Bezerra de; Magalhães, Jurandy Júnior Ferraz de; Donadi, Eduardo Antônio; Souza, Ariani Impieri; Lucena-Silva, Norma (Frontiers in Immunology, 2025)
Starting June 2021, in Brazil, the COVID-19 vaccination campaign prioritized pregnant and postpartum women to use the mRNA-based BNT162b2 (Comirnaty) vaccine, the preferred choice due to its safety profile. Although mRNA vaccines are generally safe, concerns about potential autoimmune side effects have arisen. This study aimed to assess the frequency of autoantibody production among pregnant women vaccinated with BNT162b2 compared to unvaccinated groups with active COVID-19, pre-eclampsia, and healthy control women. We studied 273 pregnant women aged 18–48 years, stratified into four groups: healthy vaccinated, healthy unvaccinated, COVID-19 positive, and pre-eclampsia. An additional control group comprised 47 healthy, non-pregnant women. Autoantibodies were detected using the HEp-2 kit (EUROIMMUN, Lübeck, SH). Statistical analysis revealed that vaccinated pregnant women exhibited a significantly lower frequency of autoantibody production compared to their unvaccinated counterparts. No significant differences in autoantibody patterns were observed between vaccinated pregnant women and the control group. Notably, control group was associated with a higher frequency of specific autoantibody patterns, including AC-4 and AC-24. These findings suggest that BNT162b2 vaccination does not increase the risk of autoimmune responses in pregnant women, contrary to some concerns. The lower frequency of autoantibody observed in vaccinated individuals may reflect beneficial immunological mechanisms, such as immune modulation and reduced viral load. Further studies are needed to explore the relationship between autoantibody production and pregnancy-related autoimmune diseases.